FAKTOR – FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN NON KEUANGAN DI BURSA EFEK INDONESIA - DANIEL HERRY SUTANTO; IGNES JANUAR CAHYADI (E-Jurnal Akuntansi TSM, 2021)
The purpose of this research is to obtain the empirical evidence about factors which influence firm value. The independent variables in this research are managerial ownership, institutional ownership, capital structure, profitability, company growth, firm size and dividend payout ratio. Dependent variable is firm value. Population in this research are non financial companies listed in Indonesian Stock Exchange from 2013-2016, where are 31 companies selected as final sample. The hypothesis in this study is tested by using multiple regression analysis. The result of this research shows capital structure, profitability and dividend payout ratio have positive influence on firm value, other than that company growth have negative influence on firm values. While managerial ownership, institutional ownership and firm size did not have influence on firm value